Last Prophet and Last Day: Shaykhī, Bābī and Bahā’ī Exegesis of the “Seal of the Prophets” (Q. 33:40) - Christopher Buck; Youli A. Ioannesyan (Religions, 2023)
The appearance of post-Islamic religions, the Bābī and Bahā’ī Faiths, is a theoretical impossibility from an orthodox Muslim perspective, since the Qur’ān designates the Prophet Muḥammad as the “Seal of the Prophets” (Q. 33:40), widely understood as meaning the “Last of the Prophets”. To overcome this problem, the respective prophet-founders, the Bāb (1819–1850) and Bahā’u’llāh (1817–1892), each presented novel approaches which this article will explore. In short, the Bāb revealed a “new” Qur’ān, i.e., the Qayyūm al-Asmā’ (1844), and Bahā’u’llāh wrote the Kitāb-i Īqān (Book of Certitude) in January 1861. While acknowledging Muḥammad as the last prophet in the “Prophetic Cycle”, the Bāb and Bahā’u’llāh inaugurated the advent of the “Cycle of Fulfillment”. This new era was foretold in the Qur’ān by way of a symbolic code, understood metaphorically and spiritually. A key concept is that of the “divine presence” (liqā’ Allāh), i.e., the encounter/“meeting” with God, whereby Q. 33:44, Q. 83:6, Q. 7:35 (and their respective parallels) effectively transcend Q. 33:40. Recognizing that the Bāb and Bahā’u’llāh each manifests the “divine presence” thereby constitutes a “realized eschatology”. This paper represents the first time that a wide-ranging survey and analysis of the Shaykhī, Bābī, and Bahā’ī viewpoints on the subject of the “Seal of the Prophets” has been made and is the result of a collaboration between two scholars working in the United States and Russia.